Tumor Response and Symptom Palliation from RAINBOW, a Phase III Trial of Ramucirumab Plus Paclitaxel in Previously Treated Advanced Gastric Cancer. (23rd December 2020) - Cascinu, Stefano; Bodoky, György; Muro, Kei; Van Cutsem, Eric; Oh, Sang Cheul; Folprecht, Gunnar; Ananda, Sumitra; Girotto, Gustavo; Wainberg, Zev A.; Miron, Maria Luisa Limon; Ajani, Jaffer; Wei, Ran; et al.
Abstract: Background: In the intent‐to‐treat (ITT) population of the RAINBOW study, objective response rate (ORR) was 28% and 16% in the ramucirumab and control arms, respectively. To further characterize tumor response, we present details on timing and extent of tumor shrinkage, as well as associations with symptom palliation. Materials and Methods: Tumor response was assessed with RECIST v1.1, and quality of life (QoL) was assessed with the European Organization for Research and Treatment of Cancer Quality‐of‐Life Questionnaire‐Core 30 (EORTC QLQ‐C30) v3.0. Prespecified and post hoc analyses were conducted in the ITT population, patients with measurable disease, or responders, and included best overall response (BOR), ORR, disease control rate (DCR), duration of response, time to response (TtR), change in tumor size, and associations of QoL with tumor shrinkage and BOR. Results: In both treatment arms, median TtR was 1.5 months. Responses were more durable in the ramucirumab versus control arm (median 4.4 vs. 2.8 months). In patients with measurable disease (78% of ITT), ORR was 36% versus 20%; DCR was 81% versus 61% in the ramucirumab versus control arms. Waterfall plots demonstrated more tumor shrinkage in the ramucirumab versus control arm. Regardless of treatment, tumor response and stable disease were associated with improved or stable QoL, with more tumor shrinkage associated with greater symptom palliation. Conclusion: Treatment with ramucirumab plus paclitaxel yielded the highest ORR reported to date for patients with previously treated advanced gastric or gastroesophageal junction adenocarcinoma. Additional details demonstrate robustness of tumor response results. The extent of tumor shrinkage is directly associated with symptom palliation and should be considered when evaluating patient needs and treatment selection. Clinical trial identification number . NCT01170663. Implications for Practice: Ramucirumab plus paclitaxel is a recognized standard of care as it improves survival for patients with advanced gastric or gastroesophageal junction adenocarcinoma who have been previously treated with recommended first‐line therapy. These additional data on tumor response demonstrate a positive association between tumor shrinkage and symptom palliation in a patient population that is often symptomatic. These observations included patients with nonmeasurable disease, a group of patients often underrepresented in clinical trials. This knowledge can inform treatment decisions, which align individual patient characteristics and needs with demonstrated benefits. Abstract : To further characterize tumor response and disease‐related symptoms from the RAINBOW study, this article presents details on timing and extent of tumor shrinkage and the association of response with symptom palliation. The reported results provide additional context for considering second‐line options for patients with advanced gastric/gastroesophageal cancer.